2021
DOI: 10.3390/cancers13071620
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade B-Cell Lymphoma (HGBL) with MYC and BCL2 and/or BCL6 Rearrangements Is Predominantly BCL6-Rearranged and BCL6-Expressing in Taiwan

Abstract: This study investigated the epidemiological and clinical peculiarities of BCL2 and BCL6 rearrangement in patients with high grade B-cell lymphoma (HGBL) from Taiwan, compared with data from Western countries. Two hundred and eighty-two DLBCL cases from Taipei Medical University-affiliated hospitals (n = 179) and Tri-Service General Hospital (n = 103) were enrolled for this study. From the 282, 47 (16.7%) had MYC translocation; 24 of these harbored concurrent BCL2 and/or BCL6 translocation (double-hit, DH or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Interestingly, we found that MYC/Bcl-2 HGBL-DH constitutes the majority of HGBL-DH in most European and American studies ( 16 , 26 29 ), such as in the United States, France, and Canada. In contrast, some studies from China’s southern regions like the Guangdong and Taiwan Provinces ( 30 , 31 ) showed that MYC/Bcl-6 HGBL-DH is the most common. We consider that it may be due to geographical differences or the relatively small number of specimens.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, we found that MYC/Bcl-2 HGBL-DH constitutes the majority of HGBL-DH in most European and American studies ( 16 , 26 29 ), such as in the United States, France, and Canada. In contrast, some studies from China’s southern regions like the Guangdong and Taiwan Provinces ( 30 , 31 ) showed that MYC/Bcl-6 HGBL-DH is the most common. We consider that it may be due to geographical differences or the relatively small number of specimens.…”
Section: Discussionmentioning
confidence: 96%
“…has recently analyzed 282 cases of DLBCL and identified 47 (16.7%) with MYC translocation, which included 24 DH/THL [ 53 ]. A total of 62.5% of the DH/THL were GCB, and DH/THL cases were associated with an unfavorable overall survival [ 53 ]. This research is similar to our project.…”
Section: Discussionmentioning
confidence: 99%
“…We did not compare with DLBCL, which was not otherwise specified. Nevertheless, we have recently shown that cases with high gene expression of BCL2 , MYC , and ENO3 are associated with an unfavorable overall survival of the patients [ 47 , 55 , 56 ], and that HGBL accounts for around 10% of the cases [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] and is characterized by higher CD163 but lower PTX3 expression [ 57 ]. Therefore, this WHO subtype is being characterized progressively.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criteria are carefully formulated in the revised 4th and 5th editions of the World Health Organisation (WHO) classification, as well as the International Consensus Classification (ICC), based on investigations in the field. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] LBCL are designated as high-grade B cell lymphoma (HGBL) based on morphological criteria. If a MYC rearrangement (MYC-R) is accompanied by BCL2 and/or BCL6, a diagnosis of HGBL with MYC and BCL2/BCL6 [also known as double-hit (DH) or triple-hit (TH) lymphoma] is made.…”
Section: Introductionmentioning
confidence: 99%